A facile synthesis of a theranostic nanoparticle by oxidation of dopamine-DTPA-Gd conjugates. Issue 44 (30th October 2017) - Xia, Mingchun; Ye, Mingzhou; Zhou, Xiaoxuan; Tang, Jianbin; Piao, Ying; Liu, Xiangrui; Zhou, Zhuxian; Hu, Hongjie; Shen, Youqing
Abstract : A theranostic nanoparticle with functions of an MRI agent and a photothermal therapy agent was facilely synthesized by oxidation of dopamine-DTPA-Gd conjugates. Abstract : Photothermal therapies (PPTs) with various light-absorbing materials have shown very promising therapeutic effects against cancers. However, their application was severely limited by the lack of accurate localization of tumors and real-time monitoring of the therapeutic process. Theranostic nanoparticles with both imaging and therapeutic functions are highly desired to develop imaging-mediated PPTs. Herein, we develop a facile one-pot method to synthesize a nanoparticle with functions of an MRI contrast agent and a PTT agent through oxidization of dopamine-DTPA-Gd conjugates and PEG-dopamine conjugates. The oxidized dopamine nanoparticles (ODNP) had a high R1 up to 9.6 mM −1 s −1, 2.2 times higher than that of Omniscan, and showed significantly higher MRI contrast enhancement than Omniscan in tumor. Meanwhile, the ODNP showed strong NIR light absorption and significant antitumor efficacy both in vitro and in vivo as a PPT agent. The ODNP with excellent MRI contrasting capability and PTT efficacy plus its facile synthesis and good biocompatibility are a very promising theranostic agent for MRI-mediated PTT.